Atomic-scale dispersed metal Cu-loaded nitrogen-doped carbon catalyst as well as preparation method and application thereof

The atomically dispersed metal Cu-supported nitrogen-doped carbon catalyst was prepared by self-assembly and pyrolyzed by Cu2+ and soluble polymer organic compounds, which solved the problem of insufficient activity and stability of Cu-based catalysts under medium and low temperature conditions, and achieved the Highly efficient and stable methanol liquid phase reforming to produce hydrogen.

CN119425754APending Publication Date: 2025-02-14DONGGUAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411559929.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing Cu-based catalysts have low activity when catalyzing methanol liquid phase reforming to produce hydrogen under medium and low temperature conditions, and the uneven metal particle size leads to poor catalyst stability.

Method used

Coordination polymer is formed by self-assembly with Cu2+ and soluble polymer organic compounds, and atomically dispersed metal Cu-supported nitrogen-doped carbon catalyst is produced by pyrolytic carbonization. The solid solution effect of carbon materials can effectively disperse nano Cu particles and prevent them from being able to prevent them. Cu loss.

Benefits of technology

The reforming hydrogen production activity and stability of Cu-based catalysts is significantly improved, the generation of CO is avoided, the production cost of catalysts is reduced, and the excellent hydrogen production performance is shown under medium and low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425754A_ABST
    Figure CN119425754A_ABST
Patent Text Reader

Abstract

The invention discloses an atomic-scale dispersed metal Cu-loaded nitrogen-doped carbon catalyst, a preparation method and application of the atomic-scale dispersed metal Cu-loaded nitrogen-doped carbon catalyst in hydrogen production by medium and low temperature methanol aqueous solution reforming. The specific surface area of the metal Cu-loaded nitrogen-doped carbon catalyst is 5-90 m < 2 > / g, and the particle size is 2-15 microns; the particle size of the metal Cu is 5-100 nm, and the content of the metal Cu is 5-55 wt%; chitosan which is low in cost and easy to obtain serves as a carbon source and a nitrogen source and also serves as a nitrogen-containing ligand, the excellent coordination capacity of chitosan is utilized to be combined with metal ions, and the metal copper-nitrogen-doped carbon material with metal particles highly dispersed, the size of the metal particles can reach the nanoscale, and the metal content can be regulated and controlled is prepared; the hydrogen production capacity of the catalyst is superior to that of a commercial Cu / ZnO / Al2O3 catalyst under medium and low temperature and alkalescence conditions, and no CO or CH4 gas is generated in a methanol liquid phase reforming product, so that the poisoning and inactivation risk of the catalyst is reduced, the service life of the catalyst is prolonged, and the catalyst is expected to replace the commercial Cu / ZnO / Al2O3 catalyst for hydrogen production by methanol liquid phase reforming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an atomic-level dispersed metal Cu-loaded nitrogen-doped carbon catalyst, a preparation method and an application thereof, and in particular to an application in a medium-low temperature methanol liquid phase reforming hydrogen production reaction. Background Art

[0002] Hydrogen energy (H2) is a green, low-carbon, and widely used energy source. It is standing out from many energy sources because of its high combustion calorific value and clean and environmentally friendly combustion products. However, H2 itself has low density, easy diffusion, and flammable and explosive characteristics, which bring difficulties to its safe storage and transportation. Therefore, the research and development of suitable hydrogen storage materials and effective hydrogen production technologies are crucial to the future development of hydrogen energy. In recent years, the in-situ release of H2 through the catalytic reforming reaction of liquid organic hydrogen carriers has provided an effective solution to the difficulties in H2 storage and transportation. Among them, methanol reforming hydrogen production is an advantageous optional technical route. First, methanol (CH3OH) is a cheap and readily available chemical raw material. The recent "Liquid Sunshine" project and traditional coal-to-methanol processes have ensured the supply of methanol; secondly, when methanol and water are reformed, an additional 1 equivalent of H2 will be further obtained from water, making the hydrogen storage density per unit mass of methanol as high as 18.75wt%, and it is a liquid at room temperature and pressure, which can be safely stored and transported, and is an excellent hydrogen storage carrier.

[0003] Methanol steam reforming (MSR) reaction can be used as a source of hydrogen fuel in fuel cells, with the advantages of cleanliness, high efficiency, and easy transportation. Catalysts are the key to the performance of methanol reforming hydrogen production. Common catalysts can be divided into two categories: one type of precious metal catalysts (such as Pt, Pd, Ru, etc.) can be used as active sites for methanol reforming hydrogen production to crack methanol, and have excellent hydrogen production performance. However, the reserves of precious metals are scarce and expensive, which limits the promotion and application of this type of catalyst. The other type is copper-based catalysts, which have the advantages of low cost, good activity, and high selectivity. It has become the most studied and applied type of catalyst. The common catalyst in industry is the three-way catalyst CuO / ZnO / Al2O3. However, Cu-based catalysts generally need to be at T>300℃ to show good hydrogen production activity, and the metal particles of Cu-based catalysts prepared by the common precipitation method are uneven in size and easy to aggregate, resulting in low catalyst activity. In addition, considering the working environment of automotive hydrogen fuel cells, the methanol reforming hydrogen production reaction needs to be carried out under mild conditions. Therefore, the development of efficient, highly active and selective Cu-based catalysts for catalytic methanol reforming to produce hydrogen under mild conditions is a current research hotspot. Summary of the invention

[0004] Based on the needs and deficiencies of the prior art, the present invention provides an atomic-level dispersed metal Cu-loaded nitrogen-doped carbon catalyst, a preparation method and an application thereof, wherein the application is an application in a medium-low temperature methanol liquid phase reforming hydrogen production reaction; the catalyst is Cu 2+ The catalyst is self-assembled with soluble high molecular weight organic matter to form a coordination polymer, and then pyrolyzed and carbonized to obtain an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst, which can overcome the shortcomings of the above-mentioned background technology.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] An atomically dispersed metal Cu-supported nitrogen-doped carbon catalyst, wherein the specific surface area of ​​the metal Cu-supported nitrogen-doped carbon catalyst is 5-90 m 2 / g, particle size is 2-15μm; metal Cu particle size is 5-100nm, and metal Cu content is 5-55wt%.

[0007] Furthermore, the specific surface area of ​​the metal Cu-supported nitrogen-doped carbon catalyst is about 9.45 m 2 / g, particle size is 7.5μm; metal Cu particle size is 70nm, and metal Cu content is 33.4wt%.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned metal Cu-supported nitrogen-doped carbon catalyst.

[0009] The preparation method comprises the following steps:

[0010] (1) adding a soluble high molecular organic matter to a dilute acid solution, adding a copper salt after sufficient stirring, and adding a transition metal salt after sufficient stirring again to obtain a mixed solution; placing the mixed solution in a water bath at a certain temperature and stirring for 2-48 hours, and then evaporating to dryness at 60-90° C. to obtain a tough precursor;

[0011] (2) placing the precursor obtained in step (1) in a tubular furnace containing an inert atmosphere for high-temperature carbonization, cooling and grinding the calcined solid to obtain the metal Cu-loaded nitrogen-doped carbon catalyst.

[0012] Furthermore, the soluble high molecular organic matter in step (1) is one or more of polyvinyl pyrrolidone, chitosan, phenolic resin, guar gum, melamine and dicyandiamide.

[0013] Furthermore, the dilute acid solution in step (1) is one or more of acetic acid, hydrochloric acid, and formic acid; and the concentration of the dilute acid solution is 0.1-10wt%.

[0014] Furthermore, the transition metal salt in step (1) is one or more of ferric nitrate, ferric acetate, ferric chloride, ferric sulfate, cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, and nickel nitrate; the addition of the transition metal salt can change the valence state of metallic copper (from Cu2+ to Cu+ / Cu0), making it easier for the catalytic reaction to proceed.

[0015] Furthermore, the copper salt in step (1) is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate, and copper acetylacetonate.

[0016] Furthermore, the stirring temperature in step (1) is 30-90° C.; and the mass ratio of the soluble high molecular organic matter, copper salt and transition metal salt in step (1) is 1:2.0-1:0.02-0.5.

[0017] Furthermore, the high temperature carbonization treatment temperature in step (2) is 300-1000°C, the carbonization time is 1-12h, and the heating rate is 0.5-10°C / min.

[0018] Furthermore, the inert atmosphere in step (2) is nitrogen or argon.

[0019] The third purpose of the present invention is to provide an application of the above-mentioned atomically dispersed metal Cu loaded nitrogen-doped carbon catalyst, characterized in that the application is an application in the medium and low temperature methanol liquid phase reforming hydrogen production reaction, using methanol aqueous solution as raw material, and producing hydrogen under the action of the atomically dispersed metal Cu loaded nitrogen-doped carbon catalyst.

[0020] The reaction process includes the following steps:

[0021] Step 1: First, a certain amount of atomically dispersed metal Cu supported nitrogen-doped carbon catalyst was reduced and activated at 250°C for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol: water mixed solution was added to the reaction system to seal the activated catalyst sample;

[0022] Step 2: Add a small amount of additives to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPaN2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0023] Step 3: The temperature of the reactor was raised to a certain temperature for 90 minutes. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0024] Furthermore, the reaction temperature is 170-250° C., further optimized to 190-230° C. The reaction pressure is 2 MPa; and the volume ratio of methanol to water in the methanol:water mixed solution is 1:1-5.

[0025] Furthermore, the auxiliary agent is one or more of ethylenediamine, KOH, K2CO3, Na2CO3 and NaOH.

[0026] Compared with the existing technology, the beneficial effects of this application are:

[0027] 1) The present invention uses Cu 2+ It self-assembles with soluble high molecular weight organic matter to form a coordination polymer, and then obtains a series of atomically dispersed metal Cu-loaded nitrogen-doped carbon catalysts through pyrolysis and carbonization. The solid solution effect of the carbon material causes the nano-Cu particles to be efficiently dispersed and effectively prevents the loss of Cu. No CO is produced when catalyzing the methanol reforming hydrogen production system, which can effectively increase the reforming hydrogen production activity and stability of the Cu-based catalyst.

[0028] 2) The atomic-level dispersed metal Cu supported nitrogen-doped carbon catalyst prepared by the present invention has a strong interaction between the metal nanoparticles and the carbon carrier, and the interface structure is controllable. In addition, the catalyst preparation method is simple, the equipment requirements are low, the raw materials are cheap and easy to obtain, and the catalyst production cost can be greatly reduced. The metal content and particle size of the prepared material are suitable and controllable.

[0029] 3) The catalyst obtained by the present invention can also be used in the fields of energy chemical industry, methanol synthesis, CO2 resource utilization, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the scheme in the embodiment of the present invention, the catalytic material obtained in the embodiment will be briefly introduced in the form of drawings.

[0031] Figure 1 This is the XRD pattern of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst obtained in Example 1 of the present invention.

[0032] Figure 2 These are the SEM (left) and TEM (right) images of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst in Example 1 of the present invention.

[0033] Figure 3 This is the Cu 2p XPS graph of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst in Example 1 of the present invention.

[0034] Figure 4 This is a graph showing the hydrogen production rate and stability of the atomically dispersed metal Cu-supported nitrogen-doped carbon catalyst obtained in Example 1 of the present invention in the methanol liquid phase reforming reaction.

[0035] Figure 5 Graph showing the hydrogen production rate of atomically dispersed metal Cu supported nitrogen-doped carbon catalysts in Examples 1-9 and Comparative Examples 1-2.

[0036] Figure 6 Graphs showing methanol conversion, hydrogen selectivity, and carbon monoxide selectivity of atomically dispersed metal Cu supported nitrogen-doped carbon catalysts in Examples 1-9 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0037] In order to make the purpose and technical solution of the present invention clearer, the present invention will be described in detail below in conjunction with Examples 1-21 and Comparative Examples 1-2, but the content included in the present invention is not limited to the embodiments given below. Based on the embodiments in the present invention, all other embodiments obtained by relevant researchers in this field without creative work are within the scope of protection of this application. In the absence of conflict, the following embodiments and their technical features can be combined with each other.

[0038] Example 1

[0039] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and after sufficient stirring, 2.4 g of Cu(NO3)2·3H2O was added, and after stirring again, 0.12 g of Fe(NO3)2·9H2O was added. The solution was placed in a 40°C water bath and stirred for 6 h, and then evaporated to dryness at 90°C to obtain a precursor;

[0040] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0041] Figure 1 This is the XRD pattern of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst synthesized in this example. It can be seen that the synthesized material contains a metal Cu phase and a weaker Cu2O phase.

[0042] Figure 2 The SEM and TEM images of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst obtained in this example show that the particle size of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst is about 7.5 μm. The TEM image shows that the metal size in the material after carbonization reduction is about 70 nm, and these metal particles are evenly distributed on the carbon material.

[0043] The specific surface area of ​​the material of this embodiment was tested by N2 physical adsorption technology. The results showed that the BET specific surface area of ​​the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst prepared in this embodiment was 9.45 m 2 / g); ICP analysis results showed that the copper content of the material was 33.4wt%.

[0044] Figure 3This is the Cu 2p XPS spectrum of the atomically dispersed metal Cu supported on nitrogen-doped carbon catalyst obtained in Example 1. The Cu 2p spectrum is divided into Cu(0<x<1) (~932.7 eV) and Cu(II) (~934 eV). The presence of the Cu(II) peak may be due to the surface oxidation of Cu species during the passivation process.

[0045] The above characterization results show that: in the atomically dispersed metal Cu supported on nitrogen-doped carbon catalyst prepared in Example 1, the main forms of Cu are metallic Cu and Cu + phase. The particle size of metallic Cu is nanoscale and uniformly dispersed. This Cu / CN catalyst will exhibit excellent hydrogen production performance in methanol reforming for hydrogen production.

[0046] Example 2

[0047] (1) Dissolve 2.0 g of polyvinylpyrrolidone in 100 mL of 0.5% acetic acid solution. After sufficient stirring, add 2.4 g of Cu(OAc)2·H2O. After stirring evenly again, add 0.12 g of Fe(NO3)2·9H2O. Place the above solution in a 60 °C water bath and stir for 6 h, then evaporate to dryness at 100 °C to obtain a precursor.

[0048] (2) Grind the above precursor evenly and place it in a high-temperature pyrolysis in a N2 atmosphere tube furnace. The pyrolysis conditions are: raise the furnace temperature from room temperature to 600 °C at a heating rate of 2 °C / min, calcine for 2 h, and after cooling and grinding the solid, obtain an atomically dispersed metal Cu supported on nitrogen-doped carbon catalyst.

[0049] Example 3

[0050] (1) Dissolve 2.0 g of chitosan in 100 mL of 0.5% acetic acid solution. After sufficient stirring, add 1.50 g of Cu(NO3)2·3H2O. After stirring evenly again, add 0.09 g of Fe(NO3)2·9H2O. Place the above solution in a 40 °C water bath and stir for 6 h, then evaporate to dryness at 80 °C to obtain a precursor.

[0051] (2) Grind the above precursor evenly and place it in a high-temperature pyrolysis in a N2 atmosphere tube furnace. The pyrolysis conditions are: raise the furnace temperature from room temperature to 700 °C at a heating rate of 2 °C / min, calcine for 2 h, and after cooling and grinding the solid, obtain an atomically dispersed metal Cu supported on nitrogen-doped carbon catalyst.

[0052] Example 4

[0053] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and after sufficient stirring, 1.0 g of Cu(NO3)2·3H2O was added, and after stirring again, 0.07 g of Fe(NO3)2·9H2O was added. The solution was placed in an 80°C water bath and stirred for 6 h, and then evaporated to dryness at 80°C to obtain a precursor;

[0054] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0055] Example 5

[0056] (1) Dissolve 2.0 g of chitosan in 100 mL of 0.5% hydrochloric acid solution, add 2.4 g of Cu(NO3)2·3H2O after sufficient stirring, stir again until uniform, add 0.12 g of Fe(NO3)2·9H2O, place the solution in a 40°C water bath, stir for 6 h, and evaporate to dryness at 80°C to obtain a precursor;

[0057] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0058] Example 6

[0059] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and after sufficient stirring, 2.4 g of Cu(NO3)2·3H2O was added, and after stirring again, 0.12 g of Fe(NO3)2·9H2O was added. The solution was placed in a 40°C water bath and stirred for 6 h, and then evaporated to dryness at 80°C to obtain a precursor;

[0060] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is raised from room temperature to 900°C at a heating rate of 2°C / min and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0061] Example 7

[0062] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and after sufficient stirring, 2.4 g of Cu(NO3)2·3H2O was added, and after stirring again, 0.12 g of Fe(NO3)2·9H2O was added. The solution was placed in an 80°C water bath and stirred for 6 h, and then evaporated to dryness at 80°C to obtain a precursor;

[0063] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is increased from room temperature to 500°C at a heating rate of 2°C / min, and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0064] Example 8

[0065] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and 2.4 g of CuCl2·2H2O was added after sufficient stirring. After stirring again, 0.12 g of Fe(NO3)2·9H2O was added. The solution was placed in an 80°C water bath and stirred for 6 h, and then evaporated to dryness at 80°C to obtain a precursor;

[0066] (2) The precursors are ground evenly and then placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are as follows: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min and calcined for 2 hours. After the solid is cooled and ground, an atomically dispersed metal Cu-loaded nitrogen-doped carbon catalyst is obtained.

[0067] Example 9

[0068] (1) 2.0 g of dicyandiamide was dissolved in 100 mL of 0.5% acetic acid solution, and 1.90 g of Cu(NO3)2·3H2O was added after sufficient stirring. After stirring again, 0.12 g of Fe(NO3)2·9H2O was added. The solution was placed in an 80° C. water bath and stirred for 6 h, and then evaporated to dryness at 80° C. to obtain a precursor;

[0069] (2) After the above precursors are ground evenly, they are placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min, and calcined for 2h. The solid is cooled and ground to obtain the Cu / C material.

[0070] Comparative Example 1

[0071] 0.60 g Cu(NO3)2·3H2O was dissolved in 2 mL deionized water, stirred for 30 min, and then 1.0 g activated carbon was added. The solution was placed in a 25°C water bath, stirred for 24 h, and then evaporated to dryness at 70°C to obtain Cu / C material.

[0072] Comparative Example 2

[0073] (1) 2.0 g of chitosan was dissolved in 100 mL of 0.5% acetic acid solution, and 1.90 g of Cu(NO3)2·3H2O was added after sufficient stirring. The solution was placed in an 80°C water bath and stirred for 6 h, and then evaporated to dryness at 80°C to obtain a precursor;

[0074] (2) After the above precursors are ground evenly, they are placed in a N2 atmosphere tubular furnace for high-temperature pyrolysis. The pyrolysis conditions are: the furnace temperature is increased from room temperature to 700°C at a heating rate of 2°C / min, and calcined for 2h. The solid is cooled and ground to obtain the Cu / C material.

[0075] Example of hydrogen production from methanol liquid phase reforming

[0076] The above-prepared series of atomically dispersed metal Cu supported nitrogen-doped carbon catalysts were used to catalyze the hydrogen production reaction of methanol liquid phase reforming, and the reaction process was as follows:

[0077] Example 10

[0078] Step 1: First, 50 mg of the catalyst of Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0079] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0080] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0081] Embodiment 11

[0082] Step 1: First, 50 mg of the catalyst of Example 2 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0083] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0084] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0085] Example 12

[0086] Step 1: First, 50 mg of the catalyst of Example 3 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0087] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0088] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0089] Example 13

[0090] Step 1: First, 50 mg of the catalyst of Example 4 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0091] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0092] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0093] Embodiment 14

[0094] Step 1: First, 50 mg of the catalyst of Example 5 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0095] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0096] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0097] Embodiment 15

[0098] Step 1: First, 50 mg of the catalyst of Example 6 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0099] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0100] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0101] Example 16

[0102] Step 1: First, 50 mg of the catalyst of Example 7 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0103] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0104] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0105] Embodiment 17

[0106] Step 1: First, 50 mg of the catalyst of Example 8 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0107] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0108] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0109] Embodiment 18

[0110] Step 1: First, 50 mg of the catalyst of Example 9 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0111] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0112] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0113] Embodiment 19

[0114] Step 1: First, 50 mg of the catalyst of Comparative Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0115] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0116] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0117] Embodiment 20

[0118] Step 1: First, 50 mg of the catalyst of Comparative Example 2 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0119] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0120] Step 3: The temperature of the reactor was raised to 210° C. for 90 min. After the temperature of the reactor dropped to room temperature, the gas phase products were collected and the products were quantitatively analyzed by gas chromatography using a single-point calibration method.

[0121] Embodiment 21

[0122] Step 1: First, 50 mg of the catalyst sample of Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a volume ratio of 1:1 was added to the reaction system to seal the activated catalyst sample;

[0123] Step 2: Add a small amount of KOH to the reaction system to absorb the product CO2 to promote the forward reaction. After purging 3 times with 2MPa N2 as the protective gas, seal the reactor and maintain a pressure of 2MPa;

[0124] Step 3: The temperature of the reactor was raised to 210°C for 90 minutes, and the gas phase product was collected after the temperature of the reactor dropped to room temperature. The reactor was then directly sealed to maintain a pressure of 2 MPa, and the reaction was continued at 210°C for 90 minutes. This process was repeated 12 times. The gas products were collected 12 times, and the products were quantitatively analyzed using gas chromatography using a single-point calibration method.

[0125] The reaction results of Examples 10-21 are shown in Figure 4 and Figure 5 , wherein SL-1 to SL-9 represent the catalysts used in Examples 10-18, respectively, and DB-1 and DB-2 represent the catalysts used in Examples 19-20, respectively.

[0126] like Figure 4 and Figure 5As shown, the Cu / CN catalyst prepared in the present invention has a high efficiency in methanol liquid phase reforming hydrogen production capacity under medium and low temperature conditions, and the catalyst is reused several times without a significant decrease in hydrogen production rate, which also shows that the prepared catalyst has good stability.

[0127] like Figure 6 As shown, SL-1 to SL-9 represent the catalysts used in Examples 10 to 18, respectively, and DB-1 and DB-2 represent the catalysts used in Examples 19 to 20, respectively. Figure 6 It is shown that the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst of the present invention has a highly efficient methanol conversion rate of about 10-15% under medium and low temperature conditions, and has good selectivity for H2 and CO.

[0128] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this field, without departing from the creative concept of the present invention, several improvements and changes can be made, which all fall within the protection scope of the present invention.

Claims

1. An atomically dispersed metal Cu supported nitrogen-doped carbon catalyst, characterized in that: The specific surface area of ​​the metal Cu-supported nitrogen-doped carbon catalyst is 5-90 m 2 / g, particle size is 2-15μm; metal Cu particle size is 5-100nm, and metal Cu content is 5-55wt%.

2. The method for preparing the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst according to claim 1, characterized in that: The preparation method comprises the following steps: (1) adding a soluble high molecular organic matter to a dilute acid solution, adding a copper salt after sufficient stirring, and adding a transition metal salt after sufficient stirring again to obtain a mixed solution; placing the mixed solution in a water bath at a certain temperature and stirring for 2-48 hours, and then evaporating to dryness at 60-90° C. to obtain a tough precursor; (2) placing the precursor obtained in step (1) in a tubular furnace containing an inert atmosphere for high-temperature carbonization, cooling and grinding the calcined solid to obtain the metal Cu-loaded nitrogen-doped carbon catalyst.

3. The preparation method according to claim 2, characterized in that: The soluble high molecular organic matter in step (1) is one or more of polyvinyl pyrrolidone, chitosan, phenolic resin, guar gum, melamine and dicyandiamide.

4. The preparation method according to claim 2, characterized in that: The dilute acid solution in step (1) is one or more of acetic acid, hydrochloric acid, and formic acid; the concentration of the dilute acid solution is 0.1-10wt%.

5. The preparation method according to claim 2, characterized in that: The transition metal salt in step (1) is one or more of ferric nitrate, ferric acetate, ferric chloride, ferric sulfate, cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate and nickel nitrate.

6. The preparation method according to claim 2, characterized in that: The copper salt in step (1) is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate and copper acetylacetonate.

7. The preparation method according to claim 2, characterized in that: The stirring temperature in step (1) is 30-90° C.; the mass ratio of the soluble high molecular organic matter, copper salt and transition metal salt in step (1) is 1:2.0-1:0.02-0.

5.

8. The preparation method according to claim 2, characterized in that: The high temperature carbonization treatment temperature in step (2) is 300-1000°C, the carbonization time is 1-12h, and the heating rate is 0.5-10°C / min.

9. The preparation method according to claim 2, characterized in that: The inert atmosphere in step (2) is nitrogen or argon.

10. Use of the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst as claimed in claim 1 or the atomically dispersed metal Cu supported nitrogen-doped carbon catalyst obtained by the preparation method of any one of claims 2 to 9, characterized in that: The application is application in medium and low temperature methanol liquid phase reforming hydrogen production reaction.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped carbon-loaded metal monoatomic catalyst

    CN108636437A

  • Nitrogen-doped carbon-supported transition metal catalyst for Knoevenagel reaction

    CN110252380A

  • Atomic-scale dispersed bimetal site anchored nitrogen-doped carbon material as well as preparation and application thereof

    CN112647095A

  • Cu-based catalyst for hydrogen production through methanol reforming, and preparation method and application thereof

    CN114160148A

  • Copper-based catalyst as well as preparation method and application thereof

    CN115582124A